2018
DOI: 10.1139/cjm-2017-0609
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid persistence: costs, benefits, and the plasmid paradox

Abstract: 22Plasmids are extrachromosomal DNA elements that can be found throughout bacteria, as well as 23 in other domains of life. Nonetheless, the evolutionary processes underlying the persistence of 24 plasmids are incompletely understood. Bacterial plasmids may encode genes for traits which are 25 sometimes beneficial to their hosts, such as antimicrobial resistance, virulence, heavy metal 26 tolerance, and the catabolism of unique nutrient sources. In the absence of selection for these 27 traits, however, plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
136
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(139 citation statements)
references
References 83 publications
3
136
0
Order By: Relevance
“…However, research has shown that, once evolved, multidrug resistance plasmids can be maintained in the absence of selection (67). There is a dearth of fitness defects reported for resistance plasmids in the literature and the reasons why some of them are evolutionarily successful are not well understood (58,68). This study demonstrates that the aac(6')-Ib-cr gene of strain M63c is carried on a large multidrug resistance plasmid pMB2, which also bears a number of genetic loci that support its evolutionary success irrespective of antibiotic selection.…”
Section: Resultsmentioning
confidence: 99%
“…However, research has shown that, once evolved, multidrug resistance plasmids can be maintained in the absence of selection (67). There is a dearth of fitness defects reported for resistance plasmids in the literature and the reasons why some of them are evolutionarily successful are not well understood (58,68). This study demonstrates that the aac(6')-Ib-cr gene of strain M63c is carried on a large multidrug resistance plasmid pMB2, which also bears a number of genetic loci that support its evolutionary success irrespective of antibiotic selection.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst these genes encoding these factors are not novel, the appearance of large aggregations of these virulence genes suggests high acquisition rates within this chromosome. The potential fitness costs associated with carrying these large islands may have resulted in the lack of plasmid content [61], although this is strictly conjecture.…”
Section: Discussionmentioning
confidence: 99%
“…In previous evolutionary studies focusing on plasmids, the burden of plasmid acquisition resulted in compensatory mutations present on host chromosomes (15,16,26,27). To identify where the resistance mutations occurred, we analyzed the genomes of six laboratory passage strains of P. stutzeri after 500 generations under conditions that selected for maintenance of megaplasmid pMPPla107.…”
Section: Described Inhibitory Agentmentioning
confidence: 99%